Discursos docentes sobre crianças cujos pais/mães vivem em condição de conjugalidade homoafetiva - Oliveira, Anna Luzia de (2016)
The family structure has been changing throughout history as a result of changes that occurred in the society. Considering these transformations, a variety of family arrangements arises, including homoparenthood , often surrounded by controversy because it is different from the prevailing heteronormativity in the society. Therefore, children placed in homosexual families is an increasing reality that exists in the society and, consequently in Brazilian schools, hence it is necessary a reflection about this fact, so that the school can contribute to the confrontation of possible stereotypes and prejudices, in order to be a place to promote and to enhance the plurality and diversity, and that is open to the coexistence of different groups and cultures. In this context, supported by the theoretical framework from the sociologist Norbert Elias and his studies about Cultural Shields, this dissertation aims to analyze speeches of teachers from public schools in Campina Grande – PB, about children whose mothers live in marital homosexual condition, and also to identify these speeches‘ characteristics, to understand how teachers deal, relate, and communicate with these children. Finally, this dissertation also aims to discuss about the possible effects of these speeches in teaching techniques. This is a qualitative study (MINAYO, 2009), that used semi-structured interviews as a research tool. Twelve teachers were interviewed, a total of 16 students the inserted in the homosexual families, all of them were women whose ages range from 29 to 54 years old. The data was analyzed based on speech analysis method proposed by Gill (2014). Based on data, it was noticed that the speeches leaned towards two different directions: some of them had a discriminatory and biased content related to the children, their mothers and to the homosexual family arrangement; and other speeches, in less quantity, leaned towards the enhancement of the family and sexual legitimacy and diversity; or at least, they acknowledged homosexual families as a reality that would not bring matters different from those problems faced by children from heterosexual families. Regarding the discriminatory and biased speeches, it was found that some interviewed women attributed any difficulty in the children‘s learning process to their families or mothers; in addition, religious arguments were frequently used to justify the ―abnormal‖ characteristic of these families. Thus, the study figured out the existence of an established-outsider connotation respectively between heterosexual families versus homosexual families, and teachers versus students that are from homosexual families, at schools. This fact points out tensions and conflicts, which deny/affirm the legitimacy of family arrangements that are different from the heterocentric standard, it also points the power that exists in this connotation. Therefore, it was possible to notice that the speeches showed that these children are still being observed and evaluated in comparison with other ones, and it represents a continuous surveillance on the homosexual effects on children. It was possible to figure out that those children are not being naturally accepted in the school environment, they even can be victims from homophobic practices.